2018
DOI: 10.1029/2018ja025639
|View full text |Cite
|
Sign up to set email alerts
|

Precipitating Electron Energy Flux and Characteristic Energies in Jupiter's Main Auroral Region as Measured by Juno/JEDI

Abstract: The relationship between electron energy flux and the characteristic energy of electron distributions in the main auroral loss cone bridges the gap between predictions made by theory and measurements just recently available from Juno. For decades such relationships have been inferred from remote sensing observations of the Jovian aurora, primarily from the Hubble Space Telescope, and also more recently from Hisaki. However, to infer these quantities, remote sensing techniques had to assume properties of the Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 54 publications
(140 reference statements)
12
69
0
Order By: Relevance
“…Broadband Alfvénic turbulence was observed at all System III longitudes but was confined to within polar latitudes immediately equatorward of the statistical auroral oval. The broadband fluctuations observed in PJ1 aligned with the broad‐energy electron signatures reported by the energetic particle instruments (Allegrini et al, ; Clark et al, ; Mauk et al, , , ). No corresponding fluctuations were observed in concert with the discrete‐energy electron signatures described by Mauk et al (, , ).…”
Section: Discussionsupporting
confidence: 69%
“…Broadband Alfvénic turbulence was observed at all System III longitudes but was confined to within polar latitudes immediately equatorward of the statistical auroral oval. The broadband fluctuations observed in PJ1 aligned with the broad‐energy electron signatures reported by the energetic particle instruments (Allegrini et al, ; Clark et al, ; Mauk et al, , , ). No corresponding fluctuations were observed in concert with the discrete‐energy electron signatures described by Mauk et al (, , ).…”
Section: Discussionsupporting
confidence: 69%
“…The black symbols correspond to the 3‐ to 30‐keV energy flux peak intervals, and the orange (blue) symbols are equatorward (polarward) of those intervals. Clark et al (2018) showed similar results for >30‐keV electrons. This study includes lower‐energy electrons (down to ~50 eV).…”
Section: Resultsmentioning
confidence: 68%
“…We calculate the characteristic energy, E char , and the energy flux, E Flux , using equations (1) and (2) in Clark et al (2018) (see also Mauk, Haggerty, Paranicas, Clark, Kollmann, Rymer, Mitchell et al (2017)): Echar=EitalicminEitalicmaxI·E0.25emnormaldEEitalicminEitalicmaxI0.25emnormaldE, and EFlux=πEitalicminEitalicmaxI·E0.25emnormaldE, where I is the particle intensity ((cm 2 ·s·sr·keV) −1 ), E is the electron energy (keV), E min is the lowest energy channel from JADE, and E max is geometric mean of the highest energy channel for JEDI, and the factor π represents the area‐projected‐weighted loss cone (see Mauk, Haggerty, Paranicas, Clark, Kollmann, Rymer, Mitchell et al (2017)). We estimate the width of the loss cone by using the simple relationship Loss Cone Angle ~asin(1/ R 3 ) 1/2 (see also Mauk, Haggerty, Paranicas, Clark, Kollmann, Rymer, Mitchell et al (2017)), where R is the Jovicentric distance in Jovian radius.…”
Section: Instruments and Datamentioning
confidence: 99%
See 2 more Smart Citations